2008
DOI: 10.1021/jf8005646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Conditions on Trace Elements in Fish Roe from Six Commercial New Zealand Fish Species

Abstract: The concentrations of trace elements in fish roes and the effect of processing conditions (karasumi-like or karashi mentaiko) were investigated in six commercial fish species from New Zealand. The studied elements were As, Cd, Cr, Cu, Hg, Pb, and Zn, and the roes were from the following species: chinook salmon ( Oncorhynchus tshawytscha), hoki ( Macruronus novaezelandiae), southern blue whiting ( Micromesistius australis), hake ( Merluccius australis), blue warehou ( Seriolella brama), and barracouta ( Thyrsit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The highest chromium contents in the female gonads and testicles analyzed in the current study were in perch at 0.197 ± 0.350 mg/kg. Bekhit, A.D. et al [ 4 ] confirmed lower values of this element at <0.05 mg/kg in the gonads of popular fishes in New Zealand. Perch from the Dniester River had similar quantities of this element at 0.08–0.25 mg/kg, while roach had much less of it at 0.01–0.02 mg/kg [ 33 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The highest chromium contents in the female gonads and testicles analyzed in the current study were in perch at 0.197 ± 0.350 mg/kg. Bekhit, A.D. et al [ 4 ] confirmed lower values of this element at <0.05 mg/kg in the gonads of popular fishes in New Zealand. Perch from the Dniester River had similar quantities of this element at 0.08–0.25 mg/kg, while roach had much less of it at 0.01–0.02 mg/kg [ 33 ].…”
Section: Discussionmentioning
confidence: 95%
“…Caviar, or sturgeon eggs, is known worldwide. It is considered to be a potential therapeutic product [ 4 ], and it is thought to have an advantageous influence on cardiovascular diseases, colon cancer, chronic inflammation, cognitive disorders, and immunomodulation. Testicles are used mainly in Asian cuisines and are considered to be an aphrodisiac.…”
Section: Introductionmentioning
confidence: 99%
“…However, fish absorb contaminants including heavy metals, and particularly toxic metals such as cadmium, lead, nickel and mercury from food and water; unfortunately, contaminants are accumulated in fish tissues (Ravanbakhsh et al, 2020). Fish absorb metals through ingesting the floating particles in water, feeding, ionexchange of dissolved metals across lipophilic membranes as in the gill, and subsequently these particles are adsorbed onto tissue and membrane surfaces (Bekhit et al, 2008). As a result of the tendency of fish to bio-accumulate and integrate pollutant loads, fish are regarded as bio-indicators of ecosystem quality (Farag et al, 2021).…”
Section: Introductionmentioning
confidence: 99%